2014
DOI: 10.1371/journal.pone.0099758
|View full text |Cite
|
Sign up to set email alerts
|

A Spatially Distinct History of the Development of California Groundfish Fisheries

Abstract: During the past century, commercial fisheries have expanded from small vessels fishing in shallow, coastal habitats to a broad suite of vessels and gears that fish virtually every marine habitat on the globe. Understanding how fisheries have developed in space and time is critical for interpreting and managing the response of ecosystems to the effects of fishing, however time series of spatially explicit data are typically rare. Recently, the 1933–1968 portion of the commercial catch dataset from the Californi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 52 publications
0
30
0
Order By: Relevance
“…We found that trophic hotspots are important fishing areas for coastal pelagic and groundfish fisheries, although in the case of fisheries for coastal pelagic species in particular, the proximity to major ports may be another contributing factor regarding the spatial distribution of catches (Miller et al. ). While it is difficult to determine the full impacts of fishing on higher trophic level species that may compete with fisheries for prey, as well as the cumulative impacts on marine ecosystems more generally, one important first step is evaluating the spatial overlap between fisheries and key ecosystem components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that trophic hotspots are important fishing areas for coastal pelagic and groundfish fisheries, although in the case of fisheries for coastal pelagic species in particular, the proximity to major ports may be another contributing factor regarding the spatial distribution of catches (Miller et al. ). While it is difficult to determine the full impacts of fishing on higher trophic level species that may compete with fisheries for prey, as well as the cumulative impacts on marine ecosystems more generally, one important first step is evaluating the spatial overlap between fisheries and key ecosystem components.…”
Section: Discussionmentioning
confidence: 99%
“…Miller et al. () provide further details and methods on the estimation of historical (1930–2000) fishery extraction patterns off California. For the purposes of this study, we summarized the total extracted metric tons (per km 2 of the appropriate habitat) of fish of each taxonomic group to the CalCOFI grid, and examined their relationship with the trophic hotpot index (biological PC).…”
Section: Methodsmentioning
confidence: 99%
“…Each ecosystem in this study has, at some stage in the last half century, experienced overfishing (Bakkala et al, 1979;Rosenberg et al, 2007;Walters et al, 2008;Link et al, 2011a;Miller et al, 2014). The impacts of overfishing are complex, but well researched.…”
Section: Thresholds As Reference Points In Managementmentioning
confidence: 97%
“…While the cause and magnitude of the decrease in length at maturity remains unknown, it is nevertheless an important consideration when comparing reproductive potential between historic and current catches and examining potential cumulative impacts of fishing on the ecosystem as a whole. As trawl fisheries in California were first initiated in the late 1800s, targeting Pacific sanddab and other shallow-water flatfish in the waters off of San Francisco (Miller et al, 2014;Scofield, 1948), even an early effort to characterize growth and reproduction (Arora, 1951) may have potentially evaluated an altered population. Regardless of the actual drivers of this shift, the results of this analysis, in concert with their characteristic broad distribution and significance to the food web, suggest that this species may represent a model organism for both monitoring and gaining a better understanding of the cumulative consequences of both fishing and climate-driven shifts in productivity and life-history characteristics through the California Current ecosystem over the next 50 years, and potentially beyond.…”
Section: Tablementioning
confidence: 99%